Wykorzystanie metod wyborów dyskretnych w badaniach koncepcji nowych produktów - Rybicka, Aneta (Concept analysis of new products with discrete choice method, 2008)
In the concept analysis of new products discrete choice method is used. The article presents concept analysis of new products – travel agencies’ offers carried out in July and August 2007 on a sample of population of Jelenia Góra, with the application of discrete choice methods. Data are collected especially for this work using a questionnaire. In the paper conditional logit model is applied to the concept analysis of new products to present which attribute’s levels are stimulants and non-stimulants for probability of offer choice.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 22, s. 195-203